Evidence for the globalisation types model integrating different trade theories. (18th December 2019) - Rüttimann, Bruno G.
This paper summarises the research performed during the last 10 years regarding the globalisation phenomenon measuring and analysing the evolution of trade globalisation of the period 2003-2015. The goal was to find evidence for a new globalisation types model. Indeed, the economic system has become more complex during recent years, the current trade models not being able to capture individually the different aspects, not being universally applicable. The evolution of globalisation has been measured with a new entropy-based metric that computes the interweavement of trade flows. The research has shown that economic world trade has been globalising during recent years but with different patterns: de-globalising for advanced economies and globalising for emerging economies. These differences can be explained with this globalisation types model.